CARDIAC MUSCLE OF THE HORSESHOE CRAB, LIMULUS POLYPHEMUS : I. Ultrastructure - Leyton, R. A. (The Rockefeller University Press, 1971)
The fine structure of the cardiac muscle of the horseshoe crab, Limulus polyphemus, has been studied with respect to the organization of its contractile material, and the structure of its organelles and the cell junctions. Longitudinal sections show long sarcomeres (5.37 µ at L(max)), wide A bands (2.7 µ), irregular Z lines, no M line, and no apparent H zone. Transverse sections through the S zone of the A band show that each thick filament is ca. 180 A in diameter, is circular in profile with a center of low density, and is surrounded by an orbit of 9–12 thin filaments, each 60 A in diameter. Thick filaments are confined to the A band: thin filaments originate at the Z band, extend through the I band, and pass into the A band between the thick filaments. The sarcolemmal surface area is increased significantly by intercellular clefts. Extending into the fiber from these clefts and from the sarcolemma, T tubules pass into the fiber at the A-I level. Each fibril is enveloped by a profuse membranous covering of sarcoplasmic reticulum (SR). Sacculations of the SR occur at the A-I boundary where they make diadic contact with longitudinal branches of the T system. These branches also extend toward the Z, enlarge at the Z line, and pass into the next sarcomere. Infrequently noted were intercalated discs possessing terminal insertion and desmosome modifications, but lacking close junctions (fasciae occludentes). These structural details are compared with those of mammalian cardiac and invertebrate muscles.